Avaliação das alterações nas frequências de ocorrência das precipitações diárias máximas para a Região Metropolitana de Belo Horizonte considerando diferentes cenários de climas futuros - David Antonio Jimenez Osorio (2022)
Climate change generates alterations in the rainfall regime, which are characterized by variations in the frequencies and intensities of precipitation, both at the daily and subdaily level. In this context, the Coupled Model Intercomparison Project (CMIP) attempts to better understand past, present, and future climate changes that arise from natural variability or as responses to changes in radiative forcing, from climate modeling of greenhouse gas emission scenarios. In this context, the present work seeks to evaluate the possible changes in the frequencies of occurrence of maximum daily precipitation per hydrological year in the metropolitan region of Belo Horizonte (RMBH), which would present themselves under the occurrence of emission scenarios SSP1-2. 6 and SSP5-8.5, in the short (2016-2043), medium (2044-2071) and long (2072-2099) term, considering Cold-Wet (FU), Cold-Dry (FS), Hot-Dry (QS) and Hot-Wet (QU) climate conditions. In order to achieve the planned objective, Downscaling techniques based on Regression Trees (RT), Genetic Programming (GP), Quantile Mapping (QM) and the Delta Method were evaluated. The results showed that for the RMBH the RA-based techniques were the best option to develop studies aiming at identifying changes in the frequency of occurrence of daily maximum rainfall, in a context of climate change. However, in the case of studies that aim to identify changes both in the number of rainy days and in the total precipitation per hydrological year, Downscaling approaches other than those based on RT, GP, QM and the Delta Method should be analyzed. The development of the frequency analysis allowed us to identify that, in general terms, the quantiles of maximum daily precipitation projected in the short, medium, and long term are within the confidence intervals (CI) of the historical quantiles, although in some cases values are projected higher and lower than the CI. Likewise, it was perceived that the increases and decreases of the projected intensities in each emission scenario vary with the return time, however, in general terms it is perceived that the longer the return time, the greater are the projected changes.